USAHA MENINGKATKAN STRATEGI PEMASARAN PADA CV. SINAR BAJA ELECTRIC DI SURABAYA (Kegiatan Pengabdian Masyarakat) : BUSINESS TO IMPROVE MARKETING STRATEGY ON CV. ELECTRIC STEEL SINAR IN SURABAYA (Community Service Activities) - Achmad Daengs GS (Jurnal Suara Pengabdian 45, 2022)
Plan strategic in competitive marketing started by analyze of competitor. Company differ value and customer satisfaction by value that be given price product,promotion, and distribution (marketing mix) on his competitor. With high competition in trading, so strategic in marketing denotes me of important thing on enhance of selling. Basically stratergy on marketing are wholl planning, integrated, and merge in marketing fuld, can give guidance about activity will be done to get reach target of marketing in compary. So strategy of marketing is very important to be needed to enhance of selling in the company, marketing strategy. Consists of price, strategy of distribution, Strategy of promotion and place four strategy above also we called by marketing mix. By four element of marketing mix above must be implemented base on level market competition will by target of company, on focus price strategy or marketing strategy analysis to enhance off selling in marble company, and another strategy four element of marketing mix improperly will make marketing activity, will be useless and spend of human resource which is issued.